1986
DOI: 10.1177/1077727x8601400303
|View full text |Cite
|
Sign up to set email alerts
|

Fashion Model's Age as an Influence on Consumers' Attitudes and Purchase Intent

Abstract: Generally, women's fashion magazines have not featured models over age 40 to communicate fashion messages to the older population. A counter‐balanced de sign was used to test whether age similarity between a message source (fashion model) and a message receiver (fashion consumer) would (1) affect consumers' attitudes toward fashion models and (2) influence consumers' purchase intent of fashion apparel. Respondent and model ages were the variables investigated. Respondents 46 and under were defined as younger (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…These findings are similar to those previously reported (Kozar & Damhorst, 2008;Steinhaus & Lapitsky, 1986). As part of the Kozar and Damhorst study, women between the ages of 60-80 indicated a stronger likelihood of purchasing clothing from retailers who use older models in their advertising.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These findings are similar to those previously reported (Kozar & Damhorst, 2008;Steinhaus & Lapitsky, 1986). As part of the Kozar and Damhorst study, women between the ages of 60-80 indicated a stronger likelihood of purchasing clothing from retailers who use older models in their advertising.…”
Section: Discussionsupporting
confidence: 81%
“…As part of the Kozar and Damhorst study, women between the ages of 60-80 indicated a stronger likelihood of purchasing clothing from retailers who use older models in their advertising. Similarly, Steinhaus and Lapitsky (1986) found that older women perceived older models as more believable, qualified, and credible when assessing fashion apparel. In the current study, perceived similarity also impacted participants' perceptions of the model's attractiveness and fashionability, and indicated a stronger purchasing intent when models were perceived as being similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations